2020
DOI: 10.1111/bjd.18983
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a ‘window of opportunity’ in hidradenitis suppurativa treated with adalimumab: a retrospective, real‐life multicentre cohort study*

Abstract: Background: The anti-tumour necrosis factor (TNF)-α adalimumab is the only licenced biologic for moderate-to-severe hidradenitis suppurativa (HS). No predictors of response have been identified so far. Objective: To identify clinical parameters predicting response to adalimumab and confirm its efficacy/ safety. Methods: Data of 389 HS patients treated with adalimumab in 21 Italian centres were reviewed. Sex, ages at onset/diagnosis/baseline, body mass index, smoking, phenotypes, previous treatments, concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 27 publications
12
112
2
3
Order By: Relevance
“…Our results show high response rates to adalimumab in agreement with previous research on adalimumab real‐life use 35,36 , Table 4. Other studies showed lower adalimumab effectiveness 37,38 . These differences might be explained by different sociodemographic and clinical characteristics and different outcome measures.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results show high response rates to adalimumab in agreement with previous research on adalimumab real‐life use 35,36 , Table 4. Other studies showed lower adalimumab effectiveness 37,38 . These differences might be explained by different sociodemographic and clinical characteristics and different outcome measures.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding clinical characteristics, in line with grouping criteria, eligible patients had more inflammatory nodules and abscesses than non- Our results show high response rates to adalimumab in agreement with previous research on adalimumab real-life use 35,36 , Table 4. Other studies showed lower adalimumab effectiveness 37,38 . Our study shows that in clinical practice, biologics are used in many severe patients where the main problem is draining tunnels and the AN count is low.…”
Section: Discussionmentioning
confidence: 91%
“…A recent real‐life multicenter study on 389 patients with HS treated with adalimumab confirmed the tolerability of the TNF‐α inhibitor; mild upper respiratory tract infections were reported and a case of serious infections pneumonia sustained by Aspergillus fumigatus probably related to the treatment was described 3 …”
Section: Factors Treated Group N (%)mentioning
confidence: 90%
“…Since the end of February, when the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic had already spread in most of Italy, a task force comprised of four dermatologists, one infectious disease specialist, one A recent real-life multicenter study on 389 patients with HS treated with adalimumab confirmed the tolerability of the TNF-α inhibitor; mild upper respiratory tract infections were reported and a case of serious infections pneumonia sustained by Aspergillus fumigatus probably related to the treatment was described. 3 In addition, similar to psoriasis, recent studies demonstrated that HS is associated with several comorbidities including smoking history, metabolic syndrome (including hypertension and diabetes), obesity, cardiovascular complications, dyslipidemia, and inflammatory bowel disease. 4 Emerging data demonstrate that risk factors for severe COVID-19 infection are strikingly similar to HS comorbidities specifically obesity, cardiovascular diseases, diabetes, hypertension, and smoking history.…”
Section: Sars-cov-2 Skin Diseasesmentioning
confidence: 99%
“…Data on golimumab are very limited. Golimumab has been used successfully in a patient suffering from concomitant HS/AI and pyostomatitis vegetans in ulcerative colitis 37 . Golimumab failed in another patient with concomitant HS/AI and psoriatic arthritis 38 …”
Section: Treatment With Biologicsmentioning
confidence: 99%